2016
DOI: 10.1586/17512433.2016.1126506
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind trial on the use of 1% hydrocortisone cream for the prevention of acute radiation dermatitis

Abstract: Five patients in each group developed moist desquamation; however, its extent and severity were milder in the steroid group. Mean ARD scores were also lower in the steroid group (0.713 vs. 0.874, p = 0.024). A lower incidence of Grades 1 and 2 radiation dermatitis was also noted in the steroid group at weeks 2 and 4, respectively, indicating prophylactic use of steroids delayed the onset of radiodermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 25 publications
0
31
0
7
Order By: Relevance
“…Statistical Power was calculated in RCTs using a two-sided test of significance (8,26,27), test was not reported for in three RCTs (28,29) and no statistical power calculation was present for four (7,(30)(31)(32). Descriptive statistics were reported in all studies for age (quantitative numerical data) including mean, median, and range (7,8,(26)(27)(28)(29)(30)(31)(32)(33). Other trials reported mean and range field size (29,33), field area (33), range of total radiation dose (7,26), median number of nodes and range (8).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Statistical Power was calculated in RCTs using a two-sided test of significance (8,26,27), test was not reported for in three RCTs (28,29) and no statistical power calculation was present for four (7,(30)(31)(32). Descriptive statistics were reported in all studies for age (quantitative numerical data) including mean, median, and range (7,8,(26)(27)(28)(29)(30)(31)(32)(33). Other trials reported mean and range field size (29,33), field area (33), range of total radiation dose (7,26), median number of nodes and range (8).…”
Section: Methodsmentioning
confidence: 99%
“…Descriptive statistics were reported in all studies for age (quantitative numerical data) including mean, median, and range (7,8,(26)(27)(28)(29)(30)(31)(32)(33). Other trials reported mean and range field size (29,33), field area (33), range of total radiation dose (7,26), median number of nodes and range (8).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations